Climate Change, Growth, and Poverty - Hull, Katy (World Bank, Washington, DC, 2012)
Equity emerged as the principal theme during the Poverty Reduction and Economic Management (PREM) week session 'climate change, growth and poverty,' where presenters addressed the distributional consequences of climate change, as well as countries' unequal capacity to cope with the twin challenges of adaptation and mitigation. They highlighted actions to strengthen the global knowledge base, bolster domestic institutions, and mobilize innovative sources of financing as immediate priorities for the World Bank and its partners.